Carbon dot synergistic biomass-based wood flame-retardant adhesive and preparation method thereof

By adding carbon dots to the wood adhesive, and by hydrothermal reaction and crosslinking technology, biomass-based wood flame retardant adhesive with excellent mechanical properties and good flame retardant properties is prepared, which solves the existing adhesive The problems of formaldehyde emission and non-renewable resources have improved the fire safety of plywood.

CN119505743APending Publication Date: 2025-02-25SOUTHWEST FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411677826.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing wood adhesives have formaldehyde release problems and dependence on non-renewable resources, and lack the biomass-based wood flame-retardant adhesives with carbon dot synergies and their preparation methods.

Method used

By mixing phlegol and ammonium polyphosphate for hydrothermal reaction, a carbon dot solution was obtained, then reacted with epoxychlorohydrin, and then crosslinked with chitosan to prepare a biomass-based wood flame retardant glue with carbon dot synergistic carbon dots to produce a carbon dot flame retardant glue. Adhesive.

Benefits of technology

This adhesive has excellent mechanical properties and good flame retardant properties, which can improve the glue strength and fire safety of plywood.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505743A_ABST
    Figure CN119505743A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dot synergistic biomass-based wood flame-retardant adhesive and a preparation method thereof, and belongs to the technical field of material science and engineering application. The preparation method comprises the following steps that three-layer plywood is prepared from the flame-retardant adhesive and poplar veneers subjected to flame-retardant treatment according to the orthogonal principle, and hot pressing is conducted to achieve adhesion. The biomass and biomass derivatives are used as raw materials, do not contain volatile substances harmful to human bodies, are safe and environment-friendly, are free of formaldehyde addition, have extremely high bonding performance, are green and environment-friendly novel biomass-based wood flame-retardant adhesive, and are short in preparation time, simple to operate, free of separation and purification of reaction products and long in storage period.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material science and engineering application technology, and in particular to a carbon point-synergistic biomass-based wood flame retardant adhesive and a preparation method thereof. Background Art

[0002] In the wood-based panel industry, the wood adhesives used in plywood are mainly formaldehyde-based phenolic resins, urea-formaldehyde resins and melamine formaldehyde resins. However, traditional formaldehyde-based adhesives have different degrees of formaldehyde release problems during the production and use of wood-based panels, and the raw materials of adhesives are mostly derived from non-renewable fossil resources such as petroleum and coal. It will also cause great harm to the surrounding living environment and people's health. Therefore, the study of green adhesives using renewable resources such as biomass as raw materials has both sustainable development significance and practical application value. Biomass materials themselves are renewable energy sources with the characteristics of biodegradability, low price, most of them are water-soluble, good environmental performance, and good processability. It is particularly important for the preparation of wood adhesives and the sustainable development of the wood processing industry. While vigorously developing the green wood industry, it is also urgent to reduce the possibility of fires caused by wood products in home decoration. Flame retardants are special chemical additives that slow down or prevent the spread of fire by reducing the flammability of materials or delaying their combustion chemical reactions. Adding flame retardants is one of the most effective ways to improve the fire safety of wood materials without affecting their structure. It is widely used in the flame retardant process of various decoration materials.

[0003] Carbon dots are a kind of spherical zero-dimensional nanocarbon material with excellent optical properties and chemical stability, good biocompatibility and low toxicity. They can be functionalized through a variety of synthesis methods to meet different application requirements. At the same time, the development of its large-scale preparation technology has laid the foundation for industrial application. The production process of carbon dots is environmentally friendly and helps to reduce environmental pollution. It has broad application prospects in many fields.

[0004] Under the background of resource depletion and the pursuit of green development, it is very necessary to research and develop a green and environmentally friendly biomass-based flame retardant adhesive with carbon dots synergistically.

[0005] Currently, there is a lack of a carbon dot-synergistic biomass-based wood flame-retardant adhesive and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide a carbon point-synergistic biomass-based wood flame retardant adhesive and a preparation method thereof.

[0007] In order to solve the problems of the prior art, the present invention provides the following technical solutions:

[0008] In a first aspect, the present application provides a carbon dot-synergistic biomass-based wood flame-retardant adhesive.

[0009] In a second aspect, the present application provides a method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive.

[0010] In a third aspect, the present application provides a method for using a carbon dot-synergistic biomass-based wood flame retardant adhesive.

[0011] In a fourth aspect, the present application provides an application of the carbon dot-synergistic biomass-based wood flame retardant adhesive in the preparation of flame retardant adhesives.

[0012] The first aspect of the present application provides a carbon dot-synergistic biomass-based wood flame retardant adhesive, and the structural formula of the biomass-based wood flame retardant adhesive is shown in formula (I): wherein n represents a multi-digit number, representing the number of repeating units in the chitosan molecule.

[0013]

[0014] The second aspect of the present application provides a method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive, comprising the following steps:

[0015] (1) mixing pyrogallol and ammonium polyphosphate with water to obtain carbon dot solution CDs through hydrothermal reaction;

[0016] (2) reacting the carbon dot solution with epichlorohydrin at 80-120° C. to obtain a mixed product

[0017]

[0018] CDs-ECH;

[0019] (3) The obtained mixed solution was added into the chitosan solution and stirred evenly at room temperature to prepare a carbon dot-synergistic biomass-based wood flame retardant adhesive, which was named CDs-ECH-CS adhesive.

[0020]

[0021] Furthermore, the mass ratio of pyrogallol to ammonium polyphosphate is 1:1.5-1:2.5; the mass ratio of the carbon dot solution to epichlorohydrin is 1:0.5-2:1.25; and the mass ratio of the mixed solution CDs-ECH to chitosan is 1:0.5-2:1.75.

[0022] Furthermore, the hydrothermal reaction conditions are 100-200° C. for 1-8 hours.

[0023] Furthermore, the preparation conditions of the mixed solution CDs-ECH are 80-120° C. and reaction time of 5-10 h.

[0024] Furthermore, the reaction conditions of the mixed solution CDs-ECH and chitosan are 4 to 12 hours at room temperature.

[0025] The second aspect of the present application provides a carbon dot-synergistic biomass-based wood flame-retardant adhesive prepared by a preparation method.

[0026] The third aspect of the present application provides a method for using a carbon dot-synergistic biomass-based wood flame retardant adhesive, which uses the carbon dot-synergistic biomass-based wood flame retardant adhesive to prepare a three-layer plywood from flame-retardant treated poplar veneer according to the orthogonal principle, and then hot presses it at 100-180°C for 4-8 minutes.

[0027] Furthermore, the method for flame retardant treatment of poplar veneer is to apply CDs on the surface of the veneer.

[0028] The use of the biomass-based wood flame-retardant adhesive provided in the fourth aspect of the present application in the preparation of a flame-retardant adhesive has good flame-retardant properties.

[0029] Beneficial effects: The present invention mixes pyrogallol and ammonium polyphosphate and burns them to obtain a carbon dot solution; the carbon dot solution and epichlorohydrin are reacted and mixed evenly, and then cross-linked with chitosan, and the obtained adhesive is a carbon dot-synergistic biomass-based wood flame-retardant adhesive. The mechanical properties of the plywood are greatly improved, which is attributed to the fact that the addition of carbon dots increases the degree of cross-linking of the adhesive, thereby greatly enhancing the cohesive force. Thereby improving the mechanical properties of the plywood. Experiments have shown that the adhesive prepared by this method has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 1 is a chemical characterization data diagram of the intermediate material CDs-ECH and the prepared adhesive CDs-ECH-CS provided in the examples of the present application. When CDs reacts with epichlorohydrin (ECH), the OH bond of CDs is 3459 cm -1 , the OH bond of CDs-ECH is 3404cm -1 ; 1040cm -1 The ether bond at 1268cm is the ether bond after the CDs and part of ECH react and open the ring; -1 The epoxy group is located at 735cm -1 The C-Cl bond of ECH is at 3000cm-1 It is the CH bond of epichlorohydrin.

[0032] Figure 2 The chemical characterization data of the intermediate material CDs-ECH and the prepared adhesive CDs-ECH-CS provided in the examples of the present application are shown in FIG. Among them, the hydrogen bond of pure chitosan (CS) is 3192 cm -1 , the hydrogen bond of comparative example 1 is 3265cm -1 , the hydrogen bond of Example 1 is 3274 cm -1 ; Among them, at 1210cm -1 In Example 1 and Comparative Example 1, it can be observed that new CN bonds are generated. DETAILED DESCRIPTION

[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0034] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0035] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0036] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0039] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0040] In a first aspect, an embodiment of the present application provides a carbon dot-synergistic biomass-based wood flame retardant adhesive, the structural formula of the biomass-based wood flame retardant adhesive is shown in formula (I): wherein n represents a multi-digit number, representing the number of repeating units in the chitosan molecule.

[0041]

[0042] The second aspect of the embodiment of the present application provides a method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive, comprising the following steps:

[0043] (1) mixing pyrogallol and ammonium polyphosphate with water to obtain carbon dot solution CDs through hydrothermal reaction;

[0044] (2) reacting the carbon dot solution with epichlorohydrin at 80-120° C. to obtain a mixed product CDs-ECH;

[0045]

[0046] (3) adding the obtained mixed solution into the chitosan solution and stirring uniformly at room temperature to prepare a carbon dot-synergistic biomass-based wood flame retardant adhesive, named CDs-ECH-CS adhesive;

[0047]

[0048] In some embodiments, the mass ratio of pyrogallol to ammonium polyphosphate is 1:1.5 to 1:2.5; the mass ratio of carbon dot solution to epichlorohydrin is 1:0.5 to 2:1.25; the mass ratio of the mixed solution CDs-ECH to chitosan is 1:0.5 to 2:1.75.

[0049] In some embodiments, the hydrothermal reaction conditions are 100-200° C. for 1-8 h.

[0050] In some embodiments, the mixed solution CDs-ECH is prepared at 80-120° C. for 5-10 hours.

[0051] In some embodiments, the mixed solution of CDs-ECH and chitosan is reacted at room temperature for 4 to 12 hours.

[0052] The second aspect of the present application provides a carbon dot-synergistic biomass-based wood flame-retardant adhesive prepared by a preparation method.

[0053] The third aspect of the present application provides a method for using a carbon dot-synergistic biomass-based wood flame retardant adhesive, which uses the carbon dot-synergistic biomass-based wood flame retardant adhesive to prepare a three-layer plywood from flame-retardant treated poplar veneer according to the orthogonal principle, and then hot presses it at 100-180°C for 4-8 minutes.

[0054] In some embodiments, the method for flame retardant treatment of poplar veneer is to apply CDs on the surface of the veneer.

[0055] The fourth aspect of the present application provides a carbon dot-synergistic biomass-based wood flame-retardant adhesive for use in the preparation of a flame-retardant adhesive having good flame-retardant properties.

[0056] The following describes the invention in conjunction with specific embodiments.

[0057] Example 1

[0058] The first aspect of the embodiment of the present application provides a carbon dot-synergistic biomass-based wood flame retardant adhesive, and the structural formula of the biomass-based wood flame retardant adhesive is shown in formula (I): wherein n represents a multi-digit number, representing the number of repeating units in the chitosan molecule.

[0059]

[0060] The second aspect of the embodiment of the present application provides a method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive, comprising the following steps:

[0061] (1) Mix 2 g of pyrogallol and 3 g of ammonium polyphosphate, add 100 mL of water to dissolve, and calcine at 160 °C for 1 h in a pressure bottle to obtain a carbon dot solution CDs;

[0062] (2) 10 g of the carbon dot solution and 5 g of epichlorohydrin were mixed, reacted at 100 °C for 3 h, and then sodium hydroxide was added and the reaction was continued for 5 h to obtain a mixed solution CDs-ECH;

[0063]

[0064] (3) 6 g of the mixed solution and 3 g of chitosan were stirred at room temperature for 8 h until they were uniform; and a carbon dot-synergistic biomass-based wood flame retardant adhesive CDs-ECH-CS was obtained.

[0065] A method for using a carbon dot-synergistic biomass-based wood flame retardant adhesive of the present invention comprises the following steps:

[0066] (1) Mix 2 g of pyrogallol and 3 g of ammonium polyphosphate, add 100 mL of water to dissolve, and calcine at 160 °C for 1 h in a pressure bottle to obtain a carbon dot solution CDs;

[0067] (2) 10 g of carbon dot solution and 5 g of epichlorohydrin were mixed and reacted at 100 °C for 3 h. Then sodium hydroxide was added and the reaction was continued for 5 h to obtain a mixed solution CDs-ECH. Its infrared characterization verified its successful preparation.

[0068] (like Figure 1 shown).

[0069] (3) 6 g of the mixed solution and 3 g of chitosan were stirred at room temperature for 8 h until they were homogeneous. The carbon dots-synergistic biomass-based wood flame retardant adhesive CDs-ECH-CS was obtained; its infrared characterization verified its successful preparation (e.g. Figure 2 shown).

[0070] Example 2

[0071] The method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive of the present invention is different from that of Example 1 only in that the amount of ammonium polyphosphate used in step (1) is 6 g, and the remaining process steps and parameters are the same as those of Example 1.

[0072] Example 3

[0073] The method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive of the present invention is different from that of Example 1 only in that the amount of ammonium polyphosphate used in step (1) is 10 g, and the remaining process steps and parameters are the same as those of Example 1.

[0074] Comparative Example 1

[0075] A method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive is different from Example 1 only in that in step (1), 2 g of pyrogallol and 3 g of ammonium polyphosphate are mixed and dissolved in 100 mL of water, and the mixture is not fired in a pressure bottle. The remaining process steps and parameters are the same as those in Example 1.

[0076] Comparative Example 2

[0077] A method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive, which is different from Comparative Example 1 only in that the amount of ammonium polyphosphate used in step (1) is 6 g, and the remaining process steps and parameters are the same as those in Comparative Example 1.

[0078] Comparative Example 3

[0079] A method for preparing a carbon dot-synergistic biomass-based wood flame-retardant adhesive, which is different from Comparative Example 1 only in that the amount of ammonium polyphosphate used in step (1) is 10g, and the remaining process steps and parameters are the same as those in Comparative Example 1.

[0080] The physical and mechanical properties of the above materials were tested using a universal mechanical testing machine, and the bonding strength of the plywood was tested according to GB / T17657-2022 standard. The bonding strength table of the results is shown in Table 1.

[0081] Table 1

[0082] Plywood test piece Bonding strength (MPa) Example 1 3.29±0.13 Example 2 2.44±0.27 Example 3 2.36±0.25 Comparative Example 1 2.12±0.2 Comparative Example 2 1.92±0.23 Comparative Example 3 1.84±0.15

[0083] From the bonding strength data in Table 1, it can be seen that the bonding performance of the plywood prepared in Example 1 is much higher than that of the plywood prepared in Examples 2-3 and Comparative Examples 1-3, which also shows that the bonding performance of the prepared plywood can be further improved after adding the carbon dot solution. The reason why the bonding performance of the plywood prepared in Example 1 is higher than that of Examples 2-3 is that the increase in the content of the flame retardant ammonium polyphosphate leads to a decrease in mechanical strength.

[0084] The flame retardant properties of plywood were tested according to the ISO 4589-2 limiting oxygen index test standard. The limiting oxygen index results are shown in Table 2.

[0085] Table 2

[0086]

[0087]

[0088] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and the scope of protection of the present invention is defined by the attached claims, description and their equivalents.

Claims

1. A carbon dot-synergistic biomass-based wood flame retardant adhesive, characterized in that: The structural formula of the biomass-based wood flame retardant adhesive is shown in formula (I): wherein n represents a multi-digit number, representing the number of repeating units in the chitosan molecule:

2. The method for preparing the carbon point-synergistic biomass-based wood flame retardant adhesive according to claim 1, characterized in that The steps include: (1) mixing pyrogallol and ammonium polyphosphate with water to obtain carbon dot solution CDs through hydrothermal reaction; (2) reacting the carbon dot solution with epichlorohydrin at 80-120° C. to obtain a mixed product CDs-ECH; (3) The obtained mixed solution was added into the chitosan solution and stirred evenly at room temperature to obtain a carbon dot-synergistic biomass-based wood flame retardant adhesive, named CDs-ECH-CS adhesive; wherein the molecular weight of chitosan ranges from 200,000 to 400,000 Da.

3. The method for preparing the carbon dot-synergistic biomass-based wood flame retardant adhesive according to claim 2, characterized in that: The mass ratio of pyrogallol to ammonium polyphosphate is 1:1.5-1:2.5; the mass ratio of the carbon dot solution to epichlorohydrin is 1:0.5-2:1.25; the mass ratio of the mixed solution CDs-ECH to chitosan is 1:0.5-2:1.

75.

4. The method for preparing the carbon dot-synergistic biomass-based wood flame retardant adhesive according to claim 2, characterized in that: The hydrothermal reaction conditions are 100-200° C. for 1-8 hours.

5. The method for preparing the carbon dot-synergistic biomass-based wood flame retardant adhesive according to claim 2, characterized in that: The preparation conditions of the mixed solution CDs-ECH are as follows: reacting at 80-120° C. for 5-10 hours.

6. The method for preparing the carbon dot-synergistic biomass-based wood flame retardant adhesive according to claim 2, characterized in that: The reaction conditions of the mixed solution CDs-ECH and chitosan are 4 to 12 hours at room temperature.

7. A method for using a carbon dot-synergistic biomass-based wood flame retardant adhesive, characterized in that: The flame-retardant treated poplar veneer is used to prepare a three-layer plywood according to the orthogonal principle using the carbon point-synergistic biomass-based wood flame-retardant adhesive described in claim 1, and then hot-pressed at 100 to 180° C. for 4 to 8 minutes.

8. The method for using the biomass-based wood flame retardant adhesive according to claim 7, characterized in that: The method for flame retardant treatment of poplar veneer is to apply CDs on the surface of the veneer.

9. The use of the biomass-based wood flame retardant adhesive according to claim 1 in the preparation of a flame retardant adhesive, characterized in that: Has good flame retardant properties.